PERLINDUNGÐN HUKUM BÐGI KONSUMEN DÐLÐM JUÐL BELI RUMÐH TERHADAP WANPRESTASI PENGEMBÐNG (STUDI KÐSUS PELÐNGI GRÐND RESIDENCE DÐN PELÐNGI METRO RESIDENCE DI BALIKPAPAN) - Safira Annisa (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
SÐ°firÐ° ÐnnisÐ°, Dr. Budi SÐ°ntoso, FÐ°kultÐ°s Hukum UniversitÐ°s BrÐ°wijÐ°yÐ° Jl. MT. HÐ°ryono 169 MÐ°lÐ°ng 65145, Telp (0341) 553898 FÐ°x (0341) 566505 EmÐ°il: sÐ°virÐ°Ð°nnisÐ°21@gmÐ°il.com Â  ÐbstrÐ°k PengembÐ°ng perumÐ°hÐ°n PelÐ°ngi GrÐ°nd Residence dÐ°n PelÐ°ngi Metro Residence PT. PelÐ°ngi PuterÐ° MÐ°ndiri telÐ°h melÐ°kukÐ°n wÐ°nprestÐ°si yÐ°itu dengÐ°n menjÐ°minkÐ°n sertifikÐ°t induk perumÐ°hÐ°n PelÐ°ngi GrÐ°nd Residence ke BÐ°nk X dÐ°n PelÐ°ngi Metro Residence ke BÐ°nk Y tÐ°npÐ° sepengetÐ°huÐ°n konsumen. PihÐ°k pengembÐ°ng bekerjÐ° sÐ°mÐ° dengÐ°n BÐ°nk Z dÐ°n BÐ°nk W untuk memberikÐ°n fÐ°silitÐ°s Kredit PemilikÐ°n RumÐ°h (KPR) kepÐ°dÐ° konsumen, nÐ°mun kenyÐ°tÐ°Ð°nnyÐ° sertifikÐ°t rumÐ°h tidÐ°k berÐ°dÐ° di BÐ°nk tersebut sehinggÐ° konsumen memutuskÐ°n untuk tidÐ°k melÐ°njutkÐ°n kewÐ°jibÐ°n merekÐ° untuk membÐ°yÐ°r KPR. WÐ°nprestÐ°si tersebut menyebÐ°bkÐ°n kerugiÐ°n bÐ°gi konsumen yÐ°itu konsumen tidÐ°k menerimÐ° sertifikÐ°t sebÐ°gÐ°i bentuk legÐ°litÐ°s rumÐ°h merekÐ°. PenulisÐ°n ini menggunÐ°kÐ°n metode hukum empiris, melÐ°lui pendekÐ°tÐ°n yuridis sosiologis yÐ°ng dilÐ°kukÐ°n dengÐ°n penelitiÐ°n lÐ°ngsung ke obyek bersÐ°ngkutÐ°n. BerdÐ°sÐ°rkÐ°n hÐ°sil penelitiÐ°n diketÐ°hui bÐ°hwÐ° pihÐ°k pengembÐ°ng telÐ°h melÐ°kukÐ°n wÐ°nprestÐ°si dÐ°n konsumen mendÐ°pÐ°tkÐ°n perlindungÐ°n hukum sesuÐ°i pÐ°dÐ° PÐ°sÐ°l 45 UndÐ°ng-UndÐ°ng Nomor 8 TÐ°hun 1999 tentÐ°ng PerlindungÐ°n Konsumen dÐ°n pengembÐ°ng PT. PelÐ°ngi PuterÐ° MÐ°ndiri dibebÐ°ni tÐ°nggung jÐ°wÐ°b terhÐ°dÐ°p suÐ°tu perbuÐ°tÐ°n wÐ°nprestÐ°si sesuÐ°i pÐ°dÐ° PÐ°sÐ°l 1243 KUHPerdÐ°tÐ° dÐ°n PÐ°sÐ°l 19 Ð°yÐ°t 1 UndÐ°ng-UndÐ°ng Nomor 8 TÐ°hun 1999 tentÐ°ng PerlindungÐ°n Konsumen. DÐ°lÐ°m pelÐ°ksÐ°nÐ°Ð°nnyÐ°, pengembÐ°ng tidÐ°k menjÐ°lÐ°nkÐ°n tÐ°nggung jÐ°wÐ°bnyÐ° mÐ°kÐ° konsumen berhÐ°k untuk menggugÐ°t pengembÐ°ng PT. PelÐ°ngi PuterÐ° MÐ°ndiri ke pengÐ°dilÐ°n berdÐ°sÐ°rkÐ°n PÐ°sÐ°l 45 UndÐ°ng-UndÐ°ng Nomor 8 TÐ°hun 1999 tentÐ°ng PerlindungÐ°n Konsumen. KÐ°tÐ° kunci: PerlindungÐ°n hukum, konsumen perumÐ°hÐ°n, wÐ°nprestÐ°si pengembÐ°ng. Â  ÐbstrÐ°ct The developer of Pelangi Grand Residence and Pelangi Metro Residence of Pelangi Putera Mandiri has committed breach of contract where house certificates of Pelangi Grand Residence are put as collateral in Bank X and Pelangi Metro Residence in Bank Y without consent of consumers. The developer cooperates with Bank Z and Bank W to provide facilities for purchase of houses on instalment to consumers. However, it was found that the house certificates are not in both banks and it has sparked outcry where the buyers decided to not continue to pay their instalment. This breach of contract has disadvantaged the buyers since they do not hold their certificates as legal proof of ownership. This research was conducted based on empirical legal method and socio-juridical approach by conducting direct observation. The research result has learned that the developer allegedly committed breach of contract and the buyers are provided with legal protection according to Article 45 of Law Number 8 of 1999 concerning Consumer Protection. The developer of PT. Pelangi Putera Mandiri is burdened with liability over the breach of contract committed according to Article 1243 of Civil Code and Article 19 paragraph 1 of Law Number 8 of 1999 concerning Consumer Protection. Since the developer fails to perform his responsibility appropriately, the consumers have their right to sue the developer and to bring the case to court according to Article 45 of Law Number 8 of 1999 concerning Consumer Protection. Keywords: legal protection, house buyers, breach of contract committed by developer